Evaluation of Training and Development Practices in SMEs: An Empirical Study - Achar, Ananthapadhmanabha (Prabandhan: Indian Journal of Management, 2013)
Small and Medium Enterprises (SMEs) play a very important role in the development of the Indian economy. This sector contributes nearly 40% to the GDP and employs about half of the labour force of the country. With the ongoing liberalization and globalization of the Indian Economy, SMEs face an increasing competition from the Global markets. Today’s global market expect reasonably priced, high quality products delivered on time. To meet this requirement, SMEs need an educated and well-trained work force. It is believed that training is a powerful agent to facilitate a firm’s expansion and the development of its capabilities, thus enhancing profitability (Cosh, Duncan, and Hughes, 1998). Hence, there is a need to provide training to the employees of Small and Medium Enterprises. Both policy makers and academicians believe that enhancing the competency of employees through Training and Development in SMEs can lead to a marked improvement in their business performance. To determine whether training programs produce real benefits for Small and Medium-size enterprises (SMEs), there is a need to evaluate the effectiveness of the training programmes. Even though the evaluation is a very important stage for a successful Training and Development (T&D) programme, this activity is the most neglected and problematic. As a result, T&D has been considered in many organizations as a waste of money and time. Despite the growing importance of SME research during the last decade, very little attention has been paid to the evaluation of the effectiveness of training programs in SMEs. In this context, the present study was undertaken to measure and assess the effectiveness of the current T&D programmes and also to analyze the challenges of evaluation of Training and Development programs in SMEs of Udupi district in Karnataka. Further, an attempt has been made in the study to identify and discuss the key facilitators and inhibitors of promoting effective Training and Development.